2004
DOI: 10.1124/jpet.104.065912
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms in Human Proton-Dependent Dipeptide Transporter PEPT1: Implications for the Functional Role of Pro586

Abstract: The human proton-dependent dipeptide transporter (PEPT1, gene SLC15A1) is important for intestinal absorption of di-and tripeptides and a variety of peptidomimetic compounds. Using a DNA polymorphism discovery panel of 44 ethnically diverse individuals, nine nonsynonymous and four synonymous coding-region single-nucleotide polymorphisms (SNPs) were identified in PEPT1. HeLa cells were transiently transfected with plasmids constructed by site-directed mutagenesis for each of the nine nonsynonymous variants. Qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 41 publications
(38 reference statements)
5
38
0
Order By: Relevance
“…Nucleotide position was confirmed by PharmGKB (Hewett et al, 2002). PEPT1 data from Zhang et al (2004b) and Anderle et al (2006). PEPT2 data from Pinsonneault et al (2004) and Terada et al (2004).…”
Section: Intestinementioning
confidence: 98%
“…Nucleotide position was confirmed by PharmGKB (Hewett et al, 2002). PEPT1 data from Zhang et al (2004b) and Anderle et al (2006). PEPT2 data from Pinsonneault et al (2004) and Terada et al (2004).…”
Section: Intestinementioning
confidence: 98%
“…Allelic diversity and haplotype distributions were determined, and nonsynonymous SNPs evaluated for functional effects, extending an earlier study (Zhang et al, 2004). Moreover, we determined allelic expression imbalance and alternative splicing to regulatory variants of PEPT1 in human intestinal samples.…”
Section: Discussionmentioning
confidence: 99%
“…For the PEPT1 substrate VAC, a significantly larger interindividual than intraindividual variability in intestinal absorption suggests the presence of genetic factors, potentially involving PEPT1 (Phan et al, 2003). In a previous sequencing study of PEPT1 involving 44 ethnically diverse individuals, 13 SNPs had been located in the coding region of PEPT1 (Zhang et al, 2004). Functional characterizations of the nine nonsynonymous SNPs revealed that only one rare variant had reduced transport activity as a result of reduced protein expression.…”
mentioning
confidence: 99%
“…The primers used for amplification and sequencing are provided in online appendix Table 1 (available at http:// diabetes.diabetesjournals.org). The PCR amplification conditions and genetic variation discovery process have been described (33).…”
Section: Methodsmentioning
confidence: 99%